Práticas educativas digitais e políticas públicas: construindo a Política Nacional de Educação Museal - Vasconcelos, Karla Colares (2018)
This research investigated a construction of a public policy for an evaluation of nature within the virtual environment. The advent of digital technologies comes ahead of the means of communication and interactions between people, an example of which are the social networks that are being disseminated in cyberspace. Training is a phenomenon, to gather in the museum environments as the auxiliary tool in the educational process of teaching and learning. Public public applications are evidenced as educational practices in information institutions. LDB -Lei n.º 9.394 / 1996- allows a wide freedom of action for the development of school projects. And, since the Declaration of Santiago (1972), it has been incorporated into the museum as pedagogical theories that education is constructed in a dialogical way. In 2012, Ibram launched a Virtual Forum for the debate on the National Program of Museum Education - PNEM, no longer a policy. In the air, from November 26, 2012 to April 7, 2013, the forum promoted the debate of nine themes, which participated in the PNEM. Since the first policies appeared in the Virtual Forum on the motivation of Ibram to change the proposal of a National Policy in a National Program. In view of this scenario, the following question was constructed: How are Brazilian public policies in the museum area fostered by the educational practices elaborated in the PNEM? To obtain a response of this kind, it is essential to: Investigate a National Policy on Muse- al Education - PNEM and its data source. As categories of analysis and discussion of the data are: Museum Education: Mae Barbosa (1991), Bruno (2007), Bemvenuti (2007); Educational Phenomena and Digital Educational Practices: Gadotti (2005), Nélisse (1997), Libâneo (2005), Freire (2010), Novak (1998); Public Educational and Historical Policies: Bobbio, Höfling; Public and Private: Arendt, Bray, Kiske, Frey; Public Educational Policies and Cultural Public Policies: Liberal, Demo, Freire, Gold; Official documents: Federal Constitution, LDB -1996, World Bank, UN and UNESCO. These studies served as the basis for the development of this work. The research is qualitative, exploratory that will count with the exploratory case study method for the field research. The field was virtual, because we conducted interviews with the participants of the Virtual Forum. The primary data were collected from semi-structured interviews and virtual logbook; while secondary data were collected through imaging data and documentary analyzes. The proposal for a more in-depth study on the development of a public policy for museum education discussed in a virtual environment meets the need to understand the current global and local events that occur in increasing numbers in cyberspace, verifying the provocations of these impacts on society and its cultural, political and educational contexts. We find that the public policies of museum education, despite being so recent, its promulgation is already threatened to spread to the entire population, as recent events in Brazilian politics warn them to remain. The event that marked society and the culture of museums was a major fire in the National Museum of Brazil - located in the city of Rio de Janeiro, where more than 20 thousand museum objects were burned. As a consequence of this fire, the federal government created a Provisional Measure 850/2018 to replace the Brazilian Institute of Museums - Ibram by the Brazilian Museums Agency - Abram, which is an autonomous social service, in the form of a private non - profit legal entity, of collective interest and public interest, in order to manage museological institutions and their collections and promote the development of the cultural and museum sector. Thus, the public policies of museum education are in the process of social construction and at the same time in danger of not being put into practice, since public spaces administered by agencies and in partnership with private institutions end up prevailing to the needs of the private institution. Thus, priority should be given to ensuring that national museums are spaces for society to see the museum as a point of non-school education. External and internal factors must preserve and maintain our cultural heritage for the access of all and the permanence of an organ that creates, develops and supervises the public policies of museums.